This I Believe - Wooten, Ben (Tufts Archival Research Center, 2006)
Director of the East Texas Chamber of Commerce, Ben Wooten, describe his belief that a divine designer rewards the hard work of individuals devoted to a worthy cause, and describes how, despite being the son of poor Texan farmers, he succeeded in his career choice as a banker.